The effect of Piriformospora indica on the root development of maize (Zea mays L.) and remediation of petroleum contaminated soil. Issue 3 (3rd March 2016) - Zamani, Javad; Hajabbasi, Mohammad Ali; Alaie, Ebrahim; Sepehri, Mozhgan; Leuchtmann, Adrian; Schulin, Rainer
ABSTRACT: As the depth of soil petroleum contamination can vary substantially under field conditions, a rhizotron experiment was performed to investigate the influence of endophyte, P. indica, on maize growth and degradation of petroleum components in a shallow and a deep-reaching subsurface layer of a soil. For control, a treatment without soil contamination was also included. The degree in contamination and the depth to which it extended had a strong effect on the growth of the plant roots. Contaminated soil layers severely inhibited root growth thus many roots preferred to bypass the shallow contaminated layer and grow in the uncontaminated soil. While the length and branching pattern of these roots were similar to those of uncontaminated treatment. Inoculation of maize with P. indica could improve root distribution and root and shoot growth in all three contamination treatments. This inoculation also enhanced petroleum degradation in soil, especially in the treatment with deep-reaching contamination, consequently the accumulation of petroleum hydrocarbons (PAHs) in the plant tissues were increased.